Cell Transplantation and "Stem Cell Therapy" in the Treatment of Myopathies: Many Promises in Mice, Few Realities in Humans. (21st October 2013) - Skuk, Daniel
Abstract : Myopathies produce deficits in skeletal muscle function and, in some cases, progressive and irreversible loss of skeletal muscles. The transplantation of myogenic cells, that is, cells able to differentiate into myofibers, is an experimental strategy for the potential treatment of some of these diseases. The objectives pursued by the transplantation of these cells are essentially three: (a) the fusion with the patient's myofibers to obtain the expression of therapeutic proteins into them, (b) the neoformation of new functional myofibers in skeletal muscles that were too degenerated by the progressive degeneration, and (c) the formation of a new pool of healthy donor-derived satellite cells. Although the repertoire of myogenic cells appears to have expanded in recent years, myoblasts are the only cells that have been demonstrated to engraft in humans. The present work aims to make a comprehensive review of the subject, from its beginnings to recent advances, including the preclinical experience in different animal models and recent clinical findings.